A critique of the policy discourse on primary health care under the Aardram mission of Kerala - Sreenidhi Sreekumar; T. K. Sundari Ravindran (Health Policy Plan., 2023)
In 2017, the State of Kerala in India, launched the 'Aardram' mission for health. One of the aims of the mission was to enhance the primary health care (PHC) provisioning in the state through the family health centre (FHC) initiative. This was envisaged through a comprehensive PHC approach that prioritized preventive, promotive, curative, rehabilitative and palliative services, and social determinants of health. Given this backdrop, the study aimed to examine the renewed policy commitment towards comprehensive PHC and the extent to which it remains true to the globally accepted ideals of PHC.This was undertaken using a critical discourse analysis (CDA) of the policy discourse on PHC. This included examining the policy documents related to FHC and Aardram as well as the narratives of policy-level actors on PHC and innovations for them. Through CDA we examined the discursive representation of PHC and innovations for improving it at the level of local governments in the state. Though the mission envisaged a shift from the influence of market-driven ideas of health, analysis of the current policy discourse on PHC suggested otherwise. The discourse continues to carry a curative care bias within its ideas of PHC. The disproportionate emphasis on strategies for early detection, treatment and infrastructural improvements meant limited space for preventive, protective and promotive dimensions, thus digressing from the gatekeeping role of PHC. The reduced emphasis on preventive and promotive dimensions and depoliticization of social determinants of health within the PHC discourse indicates that, in the long run, the mission puts at risk its stated goals of social justice and health equity envisioned in the FHC initiative.
Keywords: Menstruation knowledge; gender equality